Narcissism and Its Discontents - Walsh, J. author. aut Link
VIII, 182 p.
Keywords: Narcissism and Its Discontents challenges the received wisdom that narcissism is only destructive of good social relations. By building on insights from psychoanalysis and critical theory it puts forward a theorisation of narcissistic sociability which redeems Narcissus from his position as the subject of negative critique.